2010
DOI: 10.1111/j.1365-2834.2010.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of team climate for innovation on well-being and stress in elderly care

Abstract: Interventions that improve the team climate and provide support for innovation may increase the possibilities for growth and self-actualization of the employees that, in turn, make them more qualified to deal with stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…Fiabane () suggested that nurses providing care to older people are more likely to experience stress related to biomechanical overload, caring for suffering people and work‐related violence risk. Dackert () found, however, a significant negative correlation between organisational climate and stress reactions. Limited studies, particularly in Jordan, have explored the sources of stress for nurses who care for older people and its relationship with working conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Fiabane () suggested that nurses providing care to older people are more likely to experience stress related to biomechanical overload, caring for suffering people and work‐related violence risk. Dackert () found, however, a significant negative correlation between organisational climate and stress reactions. Limited studies, particularly in Jordan, have explored the sources of stress for nurses who care for older people and its relationship with working conditions.…”
Section: Introductionmentioning
confidence: 98%
“…2007). A better team climate has been associated with older people care nursing staff’s better well‐being and lower levels of stress (Dackert 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that when employees perceive low organizational justice, their stress levels (22,23), intra-group conflicts (24) and workgroup misbehaviors increase (25). Poor teamwork creates inadequate program organization, which results in nurses' stress (26) and may further cause assaults on psychiatric wards (7,27).…”
Section: Introductionmentioning
confidence: 99%